Investigating the role of lysis proteins of enzymatic colicins in bacterial competition - Kim, Young Chan (2017)
Colicins (Cols) are plasmid-encoded toxins produced by Escherichia coli that kill other E. coli and other closely related gram-negative species. Colicins play important role in promoting microbial diversity and provide selective advantage to the producers both as an offensive and defensive weapon. This study was set out to elucidate a better understanding of the evolution and diversity of the colicin productions within microbial community where there are more than one colicin producing strains. In the first part of the study, the factors that contribute to the observed competitive advantages of ColE9 producers over ColE7 producers were investigated. To measure the degree of cell lysis, mitomycin sensitivity (MMC) assays were carried out which demonstrated that only ColE7 producing cells undergo significant cell lysis due to the induction of ColE7 lysis gene by MMC. Growth curve assays with colicins have shown that ColE7 has faster speed of cell entry and killing than ColE9. Spot tests were carried out to test the synthesis and release of colicins which have shown that ColE7 is produced quicker in greater amounts and released more efficiently than ColE9. The lux reporter assays were carried out to test the protection conferred by immunity proteins against cognate and non-cognate colicins. It was suggested that Im9 may have greater protection against non-cognate ColE7 at higher concentrations. To investigate the roles of lysis genes, the lysis genes of ColE9 and ColE7 were swapped. Interestingly, ColE7 producers containing (ColE9 lysis genes) had competitive advantage over ColE9 producers (ColE7 lysis gene). This reversed outcome strongly suggests that the differences in the level of lysis gene expression may play an important role during the competition between ColE9 and ColE7 producing cells. Biological activity assays and the real-time dual fluorescent reporter assays have suggested that ColE7 is produced faster in larger quantities due to stronger promoter activity of ColE7 which may also account for greater expression of ColE7 lysis gene. A model has been proposed to summarise the factors involved in the competition between ColE9 and ColE7 producing E. coli cells in an unstructured well mixed environment.